2D Zn‐Porphyrin‐Based Co(II)‐MOF with 2‐Methylimidazole Sitting Axially on the Paddle–Wheel Units: An Efficient Electrochemiluminescence Bioassay for SARS‐CoV‐2. (26th September 2022) - Li, Yi‐Xuan; Li, Jing; Zhu, Dunru; Wang, Ju‐Zheng; Shu, Guo‐Fang; Li, Junji; Zhang, Sheng‐Li; Zhang, Xue‐Ji; Cosnier, Serge; Zeng, Hai‐Bo; Shan, Dan
Abstract: High electrocatalytic activity with tunable luminescence is crucial for the development of electrochemiluminescence (ECL) luminophores. In this study, a porphyrin‐based heterobimetallic 2D metal organic framework (MOF), [(ZnTCPP)Co2 (MeIm)] (1), is successfully self‐assembled from the zinc(II) tetrakis(4‐carboxyphenyl)porphine (ZnTCPP) linker and cobalt(II) ions in the presence of 2‐methylimidazole (MeIm) by a facile one‐pot reaction in methanol at room temperature. On the basis of the experimental results and the theoretical calculations, the MOF 1 contains paddle–wheel [Co2 (‐CO2 )4 ] secondary building units (SBUs) axially coordinated by a MeIm ligand, which is very beneficial to the electron transfer between the Co(II) ions and oxygen. Combining the photosensitizers ZnTCPP and the electroactive [Co2 (‐CO2 )4 ] SBUs, the 2D MOF 1 possesses an excellent ECL performance, and can be used as a novel ECL probe for rapid nonamplified detection of the RdRp gene of SARS‐CoV‐2 with an extremely low limit of detection (≈30 aM). Abstract : A novel porphyrin‐based heterobimetallic 2D MOF, [(ZnTCPP)Co2 (MeIm)] (1) is constructed to act as an excellent electrochemiluminescence probe for rapid nonamplified detection of SARS‐CoV‐2.